Formulado a base de alecrim para controle de Alternaria brassicae e Xanthomonas campestris pv. campestris em couve folha - Mata, Tatiane Calandrino da (2022)
Studies have shown the potential of medicinal plants to control plant diseases, both by direct antimicrobial action and indirect action, through the activation of plant defense mechanisms against pathogens. The objective of this work was to evaluate the antimicrobial and resistance mechanism induction activities in leafy cabbage against Xanthomonas campestris pv. campestris (Xcc) and Alternaria brassicae, from chemical and organic formulations based on rosemary (Rosmarinus officinalis). The treatments at 0%, 0.5%, 1%, 2%, 4% and 6% concentrations of All Crim ConventionalTM and All Crim OrganicTM foliar fertilizers were used in vitro assays to evaluate bacterial multiplication and mycelial growth, sporulation and germination of spores of A. brassicae and, in vivo trials, to evaluate the severity and biochemical analysis of the enzymes peroxidase, polyphenoloxidase and phenylalanine ammonia-lyase (FAL), as well as to evaluate agronomic variables (fresh and dry mass of aerial part, root volume, leaf area and chlorophyll content). The rosemary-based chemical and organic formulations reduced Xcc growth up to 74.5% and 54.8%, respectively. There was inhibition of mycelial growth by 40% and 33%, sporulation by 61.35% and 54.5% and germination of conidia of A. brassicae by 77.41% and 68.22% in the chemical and organic formulates, respectively. For disease intensity, there was a reduction of 37% and 35% in the severity black rot, while for alternaria spot there was a reduction of 61.29% and 56.30% in the chemical and organic formulations, respectively. In the in vivo assays, there were no differences between the treatments for fresh and dry masses of aerial part, root volume, leaf area and chlorophyll content, however, the chemical and organic formulations induced peroxidase and FAL activity both locally and systemically in leafy cabbage challenged with X. campestris pv. campestris and A. brassicae. This indicates the action of elicitors present in these rosemary-based formulations, with dose-dependent effect for the activation of these defense mechanisms.